IMPROVING THE METHOD OF ASSESSING THE EFFECTIVENESS OF MARKETING STRATEGY OF INDUSTRIAL ENTERPRISES - Umarova Maxfuza Ne`matovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article examines the issue of improving the method of evaluating the effectiveness of the future development marketing strategy of cotton ginning enterprises.